The better I feel, the better I can do: The role of leaders' positive affective presence. (April 2019) - Jiang, Jing; Gu, Huimin; Dong, Yanan; Tu, Xingyong
Highlights: Leader positive affective presence has a positive effect on employee service performance. Employee energy at work plays a mediating role between leader positive affective presence and employee service performance. Service climate moderates the indirect effect of leader positive affective presence on employee service performance. Abstract: This study adopts the affect theory of social exchange to examine the influence of leaders' positive affective presence on employees' service performance via employees' energy at work and the moderating role of service climate. Based on 383 dyads of leaders and their employees in the hospitality industry, the results reveal that leaders' positive affective presence has a positive effect on employees' service performance. Employees' energy at work mediates the relationship between leaders' positive affective presence and employees' service performance. Service climate enhances the relationship of employees' energy at work and service performance, which in turn strengthens the indirect effect of leaders' positive affective presence on employees' service performance via employees' energy at work.